2018
DOI: 10.1016/j.neurobiolaging.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Genetic screening in two Iranian families with early-onset Alzheimer's disease identified a novel PSEN1 mutation

Abstract: A subset of early-onset Alzheimer's disease is inherited as an autosomal-dominant trait and is associated with mutations in the genes encoding β-amyloid precursor protein, presenilin 1, or presenilin 2. In this study, we identified 2 PSEN1 mutations (1 novel and 1 known) in 2 unrelated Iranian families with autosomal-dominant Alzheimer's disease. The disease progressed rapidly with a mean age at onset of 33 and 42 years and an age at death ranging from 43 to 48 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…With the development of this technology, CRISPR/Cas9 gene editing system has been extensively applied to gene engineering such as genes knocking-in of mammalian cells (Banan, 2020), human diseases modeling (Torres-Ruiz and Rodriguez-Perales, 2017) and gene therapy, etc. In recent years, the CRISPR/Cas9 technology has improved dramatically over the past decade, and the efficiency of CRISPR/Cas9 system can be greatly increased by lipid-encapsulated gold nanoparticles as a multifunctional vehicle enabling a more effective therapy for tumor (Wang et al, 2018a). By means of the application of artificial virus, CRISPR/Cas9 system has many advantages such as minimum side effects, high efficiency and security over other superinfect and lipofectamine methods (Li et al, 2017).…”
Section: The Development Of Crispr/cas9 System and Its Advantages Over Other Gene-editing Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of this technology, CRISPR/Cas9 gene editing system has been extensively applied to gene engineering such as genes knocking-in of mammalian cells (Banan, 2020), human diseases modeling (Torres-Ruiz and Rodriguez-Perales, 2017) and gene therapy, etc. In recent years, the CRISPR/Cas9 technology has improved dramatically over the past decade, and the efficiency of CRISPR/Cas9 system can be greatly increased by lipid-encapsulated gold nanoparticles as a multifunctional vehicle enabling a more effective therapy for tumor (Wang et al, 2018a). By means of the application of artificial virus, CRISPR/Cas9 system has many advantages such as minimum side effects, high efficiency and security over other superinfect and lipofectamine methods (Li et al, 2017).…”
Section: The Development Of Crispr/cas9 System and Its Advantages Over Other Gene-editing Technologiesmentioning
confidence: 99%
“…Inspiringly, the expression of Cas9 protein was initially found after 24 h, and TIPS fluorescence was detected in most cells (Jo et al, 2020). In addition, Wang et al (2018a) reported a strategy to deliver Cas9-sgPlk-1 plasmids (CPs) which is condensed on TAT peptide-modified Au nanoparticles (AuNPs/CP, ACP) via electrostatic interactions, following lipid-encapsulated and lasercontrolled. This method for CRISPR/Cas9 delivery is highly efficient (Wang et al, 2018a).…”
Section: Plasmid-based Approachesmentioning
confidence: 99%
“…Hcy level changes AD development by inducing neuronal DNA damage, neuroinflammation, apoptosis, and autophagy abnormalities [ 117 119 ]. Genetic variation affects the relevant genes, which advances the age of onset and accelerates cognitive function decline [ 120 , 121 ].…”
Section: Homocysteine In Alzheimer's Diseasementioning
confidence: 99%
“…Many theories about pathological processes can be learned from literature including genetics which can play a role in some types of familiar and early-onset degenerative disorders of Alzheimer type (9)(10)(11) and be a link between immunity and the disease (12,13). When searching the molecular processes related to Alzheimer disease, two dominant pathological hallmarks were identifi ed.…”
Section: Current Therapy and The Major Pathological Processes Relatedmentioning
confidence: 99%